Technological properties of improved haricot bean (Phaseolus vulgaris L.) varieties cultivated in Ethiopia - Endris Hussen Ahmed; Tilahun A. Teka; Kumela Dibaba Tolera; Habtamu Fekadu Gemede; Kedir Ebrahim Hussen (Applied Food Research)
Despite extensive research on agronomic and nutritional aspects, studies on the technological properties of newly released haricot bean varieties in Ethiopia remain limited. This study examines the geometrical, functional, and physical properties of six varieties, revealing significant variations in seed dimensions with DAB 96 having the longest length (15.1 mm), BZ 2 the narrowest width (6.25 mm), and Ado the greatest thickness (7.02 mm). Differences in sphericity and aspect ratio were also observed with Ado showing the highest sphericity (69.9 %) and Tafach the lowest aspect ratio (0.434). Functionally, DAB 96 exhibited the highest hydration capacity (0.351 g/seed), while Tafach had the lowest (0.195 g/seed), and cooking times varied significantly, with DAB 96 requiring the shortest time (24 min). These findings are crucial for the food industry, manufacturing, and production optimization as they inform the design of processing equipment tailored to specific bean dimensions, and guide the development of efficient processing techniques to reduce energy consumption and improve product consistency. Additionally, the study provides criteria for selecting bean varieties that align with industrial requirements, such as faster cooking times or higher hydration capacity, enhancing production efficiency, product quality, and sustainability in the haricot bean value chain to meet global food market demands.